N,N-chelated nickel catalysts for highly branched polyolefin elastomers: a survey - Qaiser Mahmood (Royal Society Open Science, 2018)
The physical properties and end applications of polyolefin materials are defined by their chain architectures and topologies. These properties can, in part, be controlled by a judicious choice of the steric and electronic properties of the catalyst and, in particular, the ligand framework. One major achievement in this field is the discovery of thermoplastic polyolefin elastomers that combine the processing and recyclable characteristics of thermoplastics with the flexibility and ductility of elastomers. These polymers are highly sought after as alternative materials to thermoset elastomers. In this perspective, works in the literature related to the development of nickel catalysts as well as their implementations for the synthesis of polyolefin elastomers are summarized in detail. Throughout the perspective, attention has been focused on developing the relationship between catalyst structure and performance, on strategies for the synthesis of polyolefin elastomer using nickel catalysts, on properties of the resultant polyolefin, such as degree of branching and crystallinity, as well as on their effects on mechanical properties. The future perspective regarding the most recent developments in single-step production of polyethylene elastomers will also be presented.